Equity Shortfalls & Failure of The Welfare State: Community Willingness to Pay for Health Care at Government Facilities in Jehlum (Pakistan) - Masud, Tayyeb Imran; Farooq, Nasir; Ghaffar, Abdul (Journal of Ayub Medical College Abbottabad, 2003)
Background: The question of willingness to pay is very crucial in planning for services. In Pakistan, the long-term issues of sustainability of health systems particularly, allocation of finances have routinely been addressed by planners with insufficient data and unclear goals. This study was conducted with the objectives to determine the demand for health care services in the community; at first level care facilities and community level and determine the willingness of the community (Willingness to pay) to participate in cost sharing mechanisms for provision of primary health care in fee for service and prepayment mechanisms. Methods: A cross sectional stratified household interview survey of 600 households was carried out in urban and rural areas of district Jehlum, to address the financial sustainability of government health care interventions at the community level and to explore the question of willingness to pay for health care and their ability to participate in the cost sharing mechanisms. Results: In response to willingness to pay at a Government facility to obtain health care 437 (72.7%) of the households expressed their willingness to pay for health care. In 72% of the cases, cost was not considered as a barrier in seeking care and only 19% of the cases considered cost as a partial barrier; the rest said that cost prohibited seeking care. A majority across all strata is willing to pay for consultation and medicines at public sector facilities, although the responses from the low income groups exhibit a slight decrease in the willingness to pay. The willingness to pay is marginally affected by income, place of residence and/or cost of the treatment incurred. Conclusion: The findings of this study suggest that the community is willing to pay for health care at the public sector facilities if payment can ensure provision of essential curative services and medications at improved quality levels. Key Words: Health Expenditures, Equity, Cost sharing, Health Services Needs and Demands